2014
DOI: 10.1002/pca.2547
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative and Quantitative Analysis of Potentilla fulgens Roots by NMR, Matrix‐assisted Laser Desorption/Ionisation with Time‐of‐Flight MS, Electrospray Ionisation MS/MS and HPLC/UV

Abstract: It is evident from these analyses that roots of P. fulgens contain flavans, including oligomeric flavanols, as major constituents followed by triterpene acids. The methods described can be applied to other Potentilla species to identify their constituents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 24 publications
0
19
0
1
Order By: Relevance
“…15 Qualitative and quantitative analysis of P. fulgens roots by nuclear magnetic resonance spectroscopy, matrix-assisted laser desorption/ionization with time-of-flight mass spectrometry (MS), electrospray ionization MS/MS and high-performance liquid chromatography/ultraviolet have also been reported. 16 Phytochemical investigations of the root parts of P. fulgens have shown the presence of a novel bioflavonoid potifulgene along with epicatechin. 17 It has also been reported that the aerial parts contain two new triterpenes, potentene-A and potentene-B, as well as three known compounds, afzelchin-4 α!8″ catechin, epiafzelechin, and rutin.…”
Section: Introductionmentioning
confidence: 99%
“…15 Qualitative and quantitative analysis of P. fulgens roots by nuclear magnetic resonance spectroscopy, matrix-assisted laser desorption/ionization with time-of-flight mass spectrometry (MS), electrospray ionization MS/MS and high-performance liquid chromatography/ultraviolet have also been reported. 16 Phytochemical investigations of the root parts of P. fulgens have shown the presence of a novel bioflavonoid potifulgene along with epicatechin. 17 It has also been reported that the aerial parts contain two new triterpenes, potentene-A and potentene-B, as well as three known compounds, afzelchin-4 α!8″ catechin, epiafzelechin, and rutin.…”
Section: Introductionmentioning
confidence: 99%
“…Several flavanols and triterpenes have been estimated in the crude extract by HPLC-UV method. Ursolic acid (0.82 ± 0.05 %) and epicatechin (0.67 ± 0.03 %) were found to be the major compounds in the tested sample of roots [19]. Antibacterial assay by agar diffusion method…”
Section: Standardization Of Extractmentioning
confidence: 99%
“…Recently, a few reports on its cancer preventing and anti-diabetic properties have been documented [16][17]. We have earlier described isolation and structure elucidation of two new triterpene compounds along with several flavan-3-ol type of compounds from roots of Potentilla fulgens [18,19]. In continuation of the phytochemical investigations and recognizing the role of polyphenols in dental caries management, we planned to undertake extensive studies to evaluate anticariogenic effects of the plant and search for anticariogenic phenolic molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Phenolic compounds, quercetin, ellagic acid and kaempferol were reported for the first time in n-butanol fraction of P. fulgens , acts as potential antioxidative and cancer chemopreventive agents [31].…”
Section: Phytochemical Constituentsmentioning
confidence: 99%